Photoinduced Electron Transfer‐Regulated Protein Labeling With a Coumarin‐Based Multifunctional Photocrosslinker. Issue 3 (14th January 2019) - Hotta, Yusuke; Kaneko, Tsukasa; Hayashi, Ryuji; Yamamoto, Akito; Morimoto, Shota; Chiba, Junya; Tomohiro, Takenori
Abstract: We developed a novel diazirine‐based photolabeling agent having a (coumarin‐4‐yl)methyl ester scaffold, which exhibited multiple photochemical properties of crosslinking, fluorogenicity and cleavage. These properties can be kinetically regulated via photoinduced electron transfer between diazirine and coumarin moieties. The C−O bond of (coumarin‐4‐yl)methyl ester can be cleaved via photochemical excitation of coumarin moiety, that function has been initially quenched by the diazirine moiety. Upon diazirine photolysis with 365‐nm light, interacting protein was stably captured with photoactivatable ligand probe. Then, the unlocked cleavage function was activated with 313 nm light, and the reaction was accelerated in a weakly‐basic solution. The crosslinked protein could be selectively isolated with attachment of a small coumarin tag on the surface. This multi‐functional labeling agent has a great potential to facilitate LC‐MS/MS‐based protein identification. Abstract : Getting an agent : A coumarin‐fused diazirine photolabeling agent exhibited multiple photochemical properties of crosslinking, fluorogenicity and cleavage, and their kinetic regulation via photoinduced electron transfer between diazirine and coumarin moieties holds great potential to facilitate the LC‐MS/MS‐based protein identification process through analysis of the labeled peptide.